Indigenous Agency in the Missionary Encounter: The Example of the Khanty and the Nenets - Eva Toulouze (Journal of Ethnology and Folkloristics, 2011)
In literature about missionary activities in western Siberia in the 19th – early 20th century, the natives are seen as passive recipients of the missionaries’ initiative, as victims of their endeavours. This article intends to present another view of the encounter, showing firstly why this erroneous vision developed and secondly how the Khanty and the Nenets are actually active in the interaction. It shows how in both cases, either by accepting or by refusing, the natives follow their own interests and their own decisions without submitting to stronger constraint against their will. While those who refused to accept the missionaries’ endeavours clearly expressed their independence, those who chose to convert did it sincerely, although their understanding of Christianity did not match the missionaries’ expectations. They did it for conscious reasons, not just yielding to the missionaries’ wishes but often being themselves the initiators. For them, Christianity is integrated in a worldview that is not based on dual oppositions. Therefore, while representatives of official Christianity do not see these natives as real Christians, they consider themselves to be so.